Connections between the roma segregation processes and home circumstances in the outskirts of Hajdúböszörmény - Mező, Barna (Acta Agraria Debreceniensis, 2012)
In order to analyze the social status of local gipsies – both inside the community and among themselves – we conducted an empirical research of 300 participants, in which we took the distinctive spatioand sociostructural features of Hajdúböszörmény into consideration. Furthermore, a second research was also carried out in which we questioned 25 prominent persons. Participants were selected in a way that the study may give a realistic picture of each of the segregated areas of the town (focusing on social, educational and realty issues), thus besides questioning professionals dealing with the concern of gipsies on a daily basis, we decided to involve representatives of the local government as well. The reports concerning the realty status of the segregated areas were supplemented with further material provided by the local government.